THE EFFECT OF AUDIO STIMULUS ON THE GAIT PERFORMANCE OF PROSTHETIC LEGS USERS IN TRAINING SYSTEMS BASED ON VIRTUAL REALITY AND MARKERLESS MOTION CAPTURE - Nurul Huda, Ashila
Gait training for above-the-knee prosthetic leg users (transfemoral) is needed as a rehabilitation program to minimize gait deviation and improve gait ability. One of effective gait rehabilitations to improve gait performance for users of prosthetic leg is treadmill training by using virtual reality. Gait training with VR is considered to simulate various running conditions (horizontal, uphill, and downhill) as found in real conditions, provide interesting and fun experience, increase user motivation, increase training efficiency, and potentially improve training results. It is important to consider using VR for gait training on a treadmill because the user will be completely isolated from the visual signals around them. This results in the user not being able to see the movement of the treadmill so that it has the potential to fall and endanger them. One of solutions that can be used is the use of audio stimulus. Apart from reducing the possibility of falling when using VR, the use of audio is also useful for improving the gait performance of prosthetic users. In each training session, gait performance measurements are needed as feedback on training achievements and input for better next training sessions. However, performance measurement in prosthetic leg training is now less effective because there is no realtime feedback mechanism. To get a feedback mechanism in real time, markerless motion capture technology can be used. This study aims to evaluate the effectiveness of a markerless motion capture system in gait evaluation of prosthetic users, identify the effect of audio stimulus on gait performance of prosthetic users, and propose a gait training system design by taking into account the results of this study. Gait performance is measured based on spatio-temporal parameters and kinematic parameters. This research was conducted on 13 prosthetic foot users. Data processing in general uses repeated measure ANOVA test, One Way ANOVA, Friedman test, Wilcoxon Post-Hoc test, Bonferroni Post-Hoc test, Wilcoxon Signed Rank Test, Paired T-Test, and Mann Whitney Test. The results showed that Kinect's markerless motion capture proved effective for evaluating kinematic gait parameters, namely hip angle and knee angle. The audio stimulus has the potential to be used in a gait training system for prosthetic leg users because it can improve gait performance. With the audio stimulus, the step length, stride length, step width, and step time on the normal foot side become larger. Meanwhile, the step length and step time on the prosthetic leg side becomes smaller with the audio stimulus to balance the gait of the normal leg side and the prosthetic leg side where in conditions without audio the step length, stride length, and step time of the prosthetic leg side is greater than the prosthetic leg side normal.